(NaPO3)6-assisted wet formation of dispersive Mg(OH)2 nanoplates. (May 2015) - Ji, Yu; Wang, Jing; Xiang, Lan
Abstract : Dispersive Mg(OH)2 hexagonal nanoplates with a diameter of 100–400 nm and a thickness of 20–40 nm were synthesised by treating the flower-like Mg(OH)2 micro-agglomerates in sodium hexametaphosphate ((NaPO3 )6 ) aqueous solution at 80°C for 12 hours. Compared with the blank experiment, the presence of 0.05 mol L −1 sodium hexametaphosphate accelerated the dissolution and recrystallisation of Mg(OH)2 owing to the complex interaction between sodium hexametaphosphate and Mg 2+, leading to the increase of [Mg 2+ ] from 1.05 × 10 −6 to 2.29 × 10 −3 mol L −1 and the formation of Mg(OH)2 with high crystallinity. Meanwhile, the adsorption of sodium hexametaphosphate on Mg(OH)2 surface led to the decrease of the zeta potential of Mg(OH)2 from 3.42 to −25.1 mV, which inhibited the aggregation and promoted the formation of dispersive Mg(OH)2 nanoplates.